Technology of machine tools - Krar, Stephen F.; Gill, Arthur, 1930-; Smid, Peter; Gill, Jonathan A.; Gerritsen, Robert J. (McGraw-Hill, 2020)
The use of computers continues to change how machine tools are used to manufacture products. Computers have improved until there are now highly sophisticated units capable of controlling the operation of a single machine, a group of machines, or even a complete manufacturing plant. Section 14, "Computer-Age Machining," now includes not only computer numerical control machine tools, such as turning and machining centers, but also newer manufacturing technologies. To increase manufacturing productivity, machine tools have been equipped with modular tooling and work-holding systems, as well as new cutting tools to produce accurate parts faster and at competitive prices--